Responsabilidad civil por injurias y calumnias en redes sociales. - Sánchez Sánchez, Edison Fabian (2023)
In this research we will present the causes of slander and libel in social networks, the repercussions of these acts that are against the good name of the people, however through various writers, doctrine and jurisprudence has been compiled enough information for the development of the topic, For the better understanding of the readers and for those who will be exposed the present thesis, it is important to emphasize that the necessary interviews were made to the Judges of the Civil Unit of Riobamba who are more experts in this subject and with their great help in answering the questions we will be able to develop the interpretation of information. The use of the different research methods will be exposed in the interpretation of the results of the surveys, through the researched doctrines it is made known that the legislature of Ecuador lacks harshness for those who make these insults and slander through social networks often go unpunished and is not given the importance and punishment they deserve these acts. The different units developed are duly grounded in accordance with the topic and the legal framework of the Ecuadorian state, thus making the research appropriate.